2008
DOI: 10.1103/physrevc.78.015202
|View full text |Cite
|
Sign up to set email alerts
|

Ratios ofN15/C12andet al.

Abstract: The (W, Q 2 ) dependence of the ratio of inclusive electron scattering cross sections for 15 N/ 12 C was determined in the kinematic ranges 0.8 < W < 2 GeV and 0.2 < Q 2 < 1 GeV 2 using 2.285 GeV electrons and the CLAS detector at Jefferson Lab. The ratios exhibit only slight resonance structure, in agreement with a simple phenomenological model and an extrapolation of deep-inelastic scattering ratios to low Q 2 . Ratios of 4 He/ 12 C using 1.6 to 2.5 GeV electrons were measured with very high statistical prec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…It was indicated that the minicup had not overflowed, so L = 1.80 cm was used in the analysis. 12 The possibility of H 2 O contamination was also investigated by a careful inspection of the elastic peak region of the count ratio [95]. No tangible evidence of an elastic peak resulting from free hydrogen was found, so we concluded that water vapor contamination was not an issue.…”
Section: Development Of the Modelmentioning
confidence: 92%
See 4 more Smart Citations
“…It was indicated that the minicup had not overflowed, so L = 1.80 cm was used in the analysis. 12 The possibility of H 2 O contamination was also investigated by a careful inspection of the elastic peak region of the count ratio [95]. No tangible evidence of an elastic peak resulting from free hydrogen was found, so we concluded that water vapor contamination was not an issue.…”
Section: Development Of the Modelmentioning
confidence: 92%
“…Specifically, a polynomial fit to the superscaling function of Ref. [94] was used, with binding energies per nucleon E s ranging from 15-20 MeV, and the effective Fermi width parameter K F used in Fermi smearing ranging from 180-260 MeV, depending on the nucleon species [95]. This function was fit to both longitudinal and transverse cross-sections in the quasi-elastic region, with values for the G E and G M form factors parametrized in Ref.…”
Section: Radiated Nuclear Cross-section Modelsmentioning
confidence: 99%
See 3 more Smart Citations